2008
DOI: 10.1163/156855508x328167
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Thermally-Activated Curing of Azobenzene-Containing Benzoxazines

Abstract: Two new benzoxazine monomers with aliphatic and aromatic substituents, as well as azobenzene moieties were synthesized and characterized by spectroscopic methods. Their thermal curing behavior in the absence of any catalyst was investigated by differential scanning calorimetry. The thermal properties of the crosslinked structures were also studied by thermogravimetric analysis. While the monomeric forms gave some indication of thermally-induced isomerization, the azo groups were shown to be fixed in the disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…[6,7] The molecular structure of polybenzoxazine offers enormous design flexibility, which allows the properties of the cured materials to be tailored for a wide range of application. [8] The newly developed resins possess unique features, namely (a) near zero volumetric change upon curing, (b) no strong acid catalyst is required for curing, (c) release of no byproducts during curing, [9][10][11] (d) low water absorption, (e) for some polybenzoxazine-based materials, T g is much higher than cure temperature, (f) high char yield, (g) excellent resistance to chemicals and UV light, (h) thermal and dimensional stability, and (i) superior electrical properties. [12][13][14] Benzoxazine monomers are typically synthesized using phenol, formaldehyde, and amine (aliphatic or aromatic) [15] as starting materials either by employing solution or solvent-less method.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] The molecular structure of polybenzoxazine offers enormous design flexibility, which allows the properties of the cured materials to be tailored for a wide range of application. [8] The newly developed resins possess unique features, namely (a) near zero volumetric change upon curing, (b) no strong acid catalyst is required for curing, (c) release of no byproducts during curing, [9][10][11] (d) low water absorption, (e) for some polybenzoxazine-based materials, T g is much higher than cure temperature, (f) high char yield, (g) excellent resistance to chemicals and UV light, (h) thermal and dimensional stability, and (i) superior electrical properties. [12][13][14] Benzoxazine monomers are typically synthesized using phenol, formaldehyde, and amine (aliphatic or aromatic) [15] as starting materials either by employing solution or solvent-less method.…”
Section: Introductionmentioning
confidence: 99%
“…However, one major disadvantage of the typical polybenzoxazines is their brittleness. Three major approaches are generally considered to overcome this problem: (1) by preparing specially designed novel monomers [26][27][28][29][30][31][32], (2) by blending with polymers or fillers and fibers [33][34][35], or (3) syhthesis of end-chain, sidechain or main-chain polybenzoxazines [36][37][38][39][40]. Among the successful approaches to overcome the inherent brittleness of the thermosets is the modification by rubber [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The benzoxazine chemistry synthesis offers a wide range of molecular design flexibility on benzoxazine monomers, which are often synthesized from primary amine, formaldehyde, and petroleum-based phenolic compound. [4][5][6][7][8] So far, several research groups have reported the synthesis of cardanol-based benzoxazine monomers from cardanol to replace part of the petroleum-based phenolic compound. [9][10][11] Very recently, in our previous study, a novel benzoxazine-based phenolic resins from the renewable resources (i.e.…”
Section: Introductionmentioning
confidence: 99%